Delamination‐Free Multifunctional Separator for Long‐Term Stability of Lithium‐Ion Batteries. Issue 12 (18th February 2019) - Lee, Sang Hyun; Kim, Jungmin; Kim, Byung‐Hyun; Yoon, Sukeun; Cho, Kuk Young
Abstract: Next‐generation lithium‐ion batteries (LIBs) that satisfy the requirements for an electric vehicle energy source should demonstrate high reliability and safety for long‐term high‐energy‐density operation. This inevitably calls for a novel approach to advance major components such as the separator. Herein, a separator is designed and fabricated via application of multilayer functional coating on both sides of a polyethylene separator. The multilayer‐coated separator (MCS) has a porous structure that does not interfere with lithium ion diffusion and exhibits superior heat resistance, high electrolyte uptake, and persistent adhesion with the electrode. More importantly, it enables high capacity retention and reduced impedance build up during cycling when used in a coin or pouch cell. These imply its promising application in energy sources requiring long‐term stability. Fabrication of the MCS without the use of organic solvents is not only environmentally beneficial but also effective at cost reduction. This approach paves the way for the separator, which has long been considered an inactive major component of LIBs, to become an active contributor to the energy density toward achieving longer cycle stability. Abstract : Delamination‐free multifunctional separator maintains persistent adhesion with the electrodes without suppression of lithium ion movement between cathode and anode through the porous structure during battery operations. This novel approach paves the way for the lithium‐ion battery separator to contribute to superior mechanical and electrochemical properties for obtaining long‐term stable cyclability.